Tourist perception, satisfaction and revisit intention on island tourism: a case of Tunku Abdul Rahman Marine Parks / Edi Rizal Kassim - Edi Rizal Kassim (2013)
This study is to explore In-depth understanding of the tourist perceptions towards the activities and services provided and to investigate the overall perception of tourist towards the activities and services provided by tour operator in Tunku Abdul Rahman Marine Park. . However, if a customer’s expectation is not met by the perceived performance, dissatisfaction experience will occur. Therefore, satisfaction, being positive or negative, can be determined by performance and regarded as a vital basis of competitive issues. The result from this study attempt to gain overall perception of tourist towards the activities, price, satisfaction and quality of services provided by tour operator in Tunku Abdul Rahman Marine Park and from the result researcher could determine the factor of behavioral intention toward the Marine Park, or island. The significance of this paper will soon help to enhance tour operator’s services and give a wonderful experience to the tourist and meet the tourist needs and wants in future. Findings clearly revealed that tourist perception on island activities, service quality and price value are positively or negatively influenced tourist satisfaction in island tourism and their intention to revisit.